A Survey On UTM TESL Undergraduates’ Reading Preference: Between Hypertexts And Books - Abdul Samad , Adlina (2010)
This research uses a survey to investigate UTM TESL undergraduates’ reading preference between Hypertexts and books. The study is very crucial as it will help to identify the strengths and also the weaknesses of the preferred type of text. Therefore, questionnaires have been distributed to UTM TESL undergraduates’ session 2007/2008 (Refer Appendix A). From the research, it has been found that UTM TESL undergraduates preferred Hypertext as compared to books. The reasons why the students preferred Hypertext are encouragements from lecturers, cost and time saving, easier and faster access, interactive and interesting, up to date and more focused. However Hypertext has several weaknesses such as reliability low, has caused health problems and also technical problems. The findings suggest that the students must be taught, exposed and trained to select reliable reading materials, exposed and taught on how to overcome the technical problems and lastly they must be aware of how to prevent the Computer caused health problems.